Kontestasi Konsepsi Religius dan Ritualitas Islam Pribumi Versus Islam Salafi di Sasak Lombok - Fitriani, Mohamad Iwan (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
This article focuses on the contestation of local Islam and salafy at Narmada, West Lombok. This tension is inevitable thing, since they have different way of understanding and realizing Islamic teaching. Local Islam wants the locality and universality co-present to actualize ideal Islamic teaching, on the contrary, salafy wants to purify Islamic teaching from any kind of local traditions. Here, Local Islam of Sasak Narmada refers to Islam which has long interaction with several indigenous belief of Sasaknese manifested in Wetu Telu and Wetu Limeand salafy refers to several (not all) salafy?s followers who interact with local Muslims. This difference brings into contestation when salafy popularize bid?ah, syncretic or syirk for local Muslims adherent in one hand and local Muslims want to save Islamic teaching from salafy in another hand. The contestation is classified into religious conceptions and ritual. Many Wetu Lime?s followers enjoy their religious conceptions and rituals without leaving several Wetu Telu traditions and without being afraid of falling into polytheism for a main reason that what they do is one means of manfesting Islamic universal values in local traditions and having no intention to be polytheist. This study shows that looking for the meaning behind the conception or observed ritual is an essential thing in diverse internal religious belief to spread peace in which theology needs to be accompanied by other perspective.